Learning object-oriented programming in C# 5.0 - Harwani, B. M (Cengage Learning, 2015)
With a focus on hands-on projects, this title presents a comprehensive guide to all the features of C# 5.0. It covers all the fundamentals, beginning with easy examples and gradually delving deeper into complex topics, providing the essential information you'll need to learn Visual C#.